Sunscreen Innovation: Development of a Water-Resistant Compact Powder Formula Based on Titanium Dioxide for Optimal UV Protection - Muliadi, Rahmat; Aspadiah, Vica; Sahumena, Muhammad Handoyo; Aftira, Nidya (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Ultraviolet (UV) radiation contributes to skin aging and damage, necessitating effective protection. Sunscreens offer a solution by absorbing, scattering, and reflecting UV radiation, especially those containing titanium dioxide, which has strong UV-blocking properties. Innovation in the form of compact powder sunscreen presents a practical and efficient daily protection approach due to its easy-to-apply formulation. Objective: This study aimed to evaluate the physical characteristics of compact powder sunscreen formulations, including organoleptic properties, pH, homogeneity, adhesion, hardness, and the effect of titanium dioxide on the Sun Protection Factor (SPF) value. Methods: Formulations were prepared and evaluated through physical tests, including organoleptic assessment, pH, homogeneity, adhesion, and hardness, as well as SPF measurement using a UV-Vis spectrophotometer. Results: Titanium dioxide contributed to the light brown color, smooth texture, and vanilla scent of the formulations. It also enhanced the SPF value. The most optimal formulation was Formula 4, containing 25% titanium dioxide, which met the desired physical criteria and achieved an SPF value of 15.06, categorized as ultra protection. Conclusion: The addition of titanium dioxide positively affected the physical characteristics and SPF value of compact powder sunscreen. Formula 4, with 25% titanium dioxide, demonstrated the best results and the highest SPF, making it the most optimal formulation for UV protection